Adaptation to dietary conditions by trehalose metabolism in Drosophila - Tetsuo Yasugi (Nature Portfolio, 2017)
Abstract Trehalose is a non-reducing disaccharide that serves as the main sugar component of haemolymph in insects. Trehalose hydrolysis enzyme, called trehalase, is highly conserved from bacteria to humans. However, our understanding of the physiological role of trehalase remains incomplete. Here, we analyze the phenotypes of several Trehalase (Treh) loss-of-function alleles in a comparative manner in Drosophila. The previously reported mutant phenotype of Treh affecting neuroepithelial stem cell maintenance and differentiation in the optic lobe is caused by second-site alleles in addition to Treh. We further report that the survival rate of Treh null mutants is significantly influenced by dietary conditions. Treh mutant larvae are lethal not only on a low-sugar diet but also under low-protein diet conditions. A reduction in adaptation ability under poor food conditions in Treh mutants is mainly caused by the overaccumulation of trehalose rather than the loss of Treh, because the additional loss of Tps1 mitigates the lethal effect of Treh mutants. These results demonstrate that proper trehalose metabolism plays a critical role in adaptation under various environmental conditions.